Introduction - Bárth, Dániel (Historical Studies on Central Europe, 2023)
The MTA-ELTE Lendület (“Momentum”) Historical Folkloristics Research Group organized a separate panel at the 16th Congress of SIEF (Société Internationale d’Ethnologie et de Folklore), the world’s largest ethnological and folklore organization, which took place in Brno, Czech Republic, in June 2023.